Analisis Kemampuan Mengenal Bentuk Geometri pada Anak Usia 5-6 Tahun di TK Canda Mulia Desa Batang Kulim 6 Kecamatan Pangkalan Kuras - Pitriyani, Pitriyani; Solfiah, Yeni; Kurnia, Rita (Innovative: Journal Of Social Science Research, 2025)
The development of geometric abilities is very important for early childhood. This research was aimed to determine the description of the ability to recognize geometric shapes in children aged 5-6 years at Canda Mulia Kindergarten, Batang Kulim Village 6, Pangkalan Kuras District. This research was used a quantitative descriptive approach. The sample to be take by researchers is 18 children at Canda Mulia Kindergarten, Batang Kulim Village, Pangkalan Kuras District. The sample was used is 18 children. The data analysis technique was used a percentage formula. The results of this research was showed that the ability to recognize geometric shapes in the aspect of recognizing geometric shapes based on color, shape and size obtained a percentage of 72.22% with the category developing according to expectations, the aspect of matching geometric objects obtained a percentage of 69.44% with the category developing according to expectations, the aspect of comparing geometric shapes obtained a percentage of 55.56% with the category starting to develop and the aspect of mentioning geometric objects obtained a percentage of 65.28%. It can be concluded that the ability to recognize geometric shapes in children aged 5-6 years at Canda Mulia Kindergarten, Batang Kulim Village reached 65.63% which is in the range of 56%-75% with the criteria of Developing According to Expectations (BSH)